Strengthening of Character Values in The Merdeka Belajar Era by Short Film Jagat Raya 2 (2023) - Sofhie Suhartini; Heris Hendriana; Ika Mustika (IKIP Siliwangi, 2023)
This study was inspired by the declining use of character education principles, particularly among adolescents, which has a negative impact on the standard of instruction in the post-Merdeka Belajar (freedom to learn) era. In this study, Jagat Raya 2 (2023), a short film produced by the Ministry of Education and Culture, Research and Technology of the Republic of Indonesia, which is used as an alternative educational system, is used to illustrate the significance of character values in the Merdeka Belajar era. Researchers employ a type of qualitative methodology. The methods of data research employed include documentation, analysis, and literature review methods. According to the study's findings, the short video Jagat Raya 2, which was produced by the Ministry of Education and Culture in 2023, contains seven different types of character values, including honesty, responsibility, intelligence, keeping one's surroundings neat and tidy, caring, creativity, and cooperation.Â In the Merdeka Belajar era, character development through short films gives students the opportunity to decide how they feel about their own decisions, while teachers can differentiate instruction and create stimuli that will encourage students to develop their human capital.